Composite forward osmosis membrane for removing micromolecular micropollutants and preparation method of composite forward osmosis membrane

Through in-situ polymerization method, SiO2 nanoparticles are uniformly dispersed in the positive permeability membrane, which solves the problems of low water flux and poor anti-pollution performance, and achieves efficient removal of small molecule micropollutants and low reverse salt flux, which is suitable for large-scale production.

CN120550658APending Publication Date: 2025-08-29ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510608666.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing positive permeability membrane has low water flux and poor anti-pollution performance. The SiO2 nanomaterial is unevenly dispersed in the membrane, resulting in a degradation of membrane structure and performance. The preparation method is complex and not suitable for large-scale production.

Method used

In situ polymerization method is adopted, by using tetramethoxysilane to uniformly distribute SiO2 nanoparticles during the interfacial polymerization process, forming a polyamide layer with chemical bonding or strong physical interaction, improving the hydrophilicity and anti-pollution performance of the film.

Benefits of technology

The uniform dispersion of SiO2 nanoparticles in the film is achieved, the water flux and anti-pollution performance are improved, the reverse salt flux is maintained, and it is suitable for efficient removal of small molecule micropollutants, and the preparation process is simple and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120550658A_ABST
    Figure CN120550658A_ABST
Patent Text Reader

Abstract

The invention discloses a composite forward osmosis membrane for removing micromolecular micropollutants and a preparation method of the composite forward osmosis membrane. The preparation method comprises the following steps: dissolving m-phenylenediamine, camphorsulfonic acid and triethylamine in a water phase; the preparation method comprises the following steps: dissolving trimesoyl chloride and tetramethoxysilane in an organic phase; fixing the base membrane on a flat plate, adding the aqueous phase solution, and then adding the organic phase solution; integrally transferring the obtained polyamide layer and the base membrane into a drying oven, and carrying out heat treatment to obtain the forward osmosis membrane. The nano-particles generated by the method are uniformly distributed, so that the agglomeration phenomenon is avoided, the uniformity of the membrane structure is ensured, and various properties of the membrane are more stable and uniform; the low reverse salt flux is guaranteed at the cost of sacrificing a certain degree of water flux, the method focuses on guaranteeing the high water flux and maintaining the low reverse salt flux at the same time, and the method is more suitable for actual production and application by maintaining the two properties within a proper range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite forward osmosis membrane for removing small-molecule micropollutants and a preparation method thereof, belonging to the field of water treatment and membrane separation science and technology. Background Art

[0002] With the acceleration of industrialization and urbanization, the accumulation of micropollutants (MPs) in aquatic environments poses a serious challenge to ecosystems and human health. Forward osmosis (FO) membrane technology is an emerging water treatment technology. As a low-energy separation technology with strong anti-pollution potential, it shows considerable potential in removing micropollutants from water compared to traditional water treatment technologies. Compared with traditional pressure-driven membrane separation technologies (such as reverse osmosis), FO technology offers significant advantages such as low energy consumption, reduced membrane fouling, and high solute retention. FO technology is a spontaneous, low-energy process that utilizes the osmotic pressure difference across the membrane to drive the spontaneous migration of water molecules from the higher chemical potential side to the lower chemical potential side. In FO systems, the FO membrane is a core component, and its performance directly determines the overall system's operating efficiency and application effectiveness. However, currently commercial FO membranes still face many unresolved issues, limiting the widespread application of this technology.

[0003] On the one hand, existing forward osmosis membranes generally have low water flux. As a key performance metric for forward osmosis membranes, water flux directly impacts the system's processing capacity. This low water flux requires a large number of membrane modules when processing large-scale water samples. This not only increases equipment costs, but also increases the system's footprint and maintenance complexity. The main reason for this low water flux is that conventional forward osmosis membranes lack optimal structural design. The internal pore structure of the membranes is not conducive to the rapid transport of water molecules. Furthermore, the membrane material's inherent hydrophilicity is insufficient, preventing it from effectively attracting water molecules through the pores. Furthermore, forward osmosis membranes exhibit poor anti-fouling properties. In practical applications, various contaminants in water samples, such as organic matter, microorganisms, colloids, and inorganic salts, are easily adsorbed or deposited on the membrane surface and within the pores, leading to membrane fouling. Membrane fouling not only reduces membrane water flux but also reduces solute retention, severely impacting the lifespan and separation performance of forward osmosis membranes. Severe membrane fouling necessitates frequent cleaning or replacement, significantly increasing system operating costs and maintenance workload.

[0004] To improve the performance of forward osmosis membranes, researchers have attempted to introduce inorganic nanomaterials into the membrane preparation process to prepare nanocomposite (TFN) forward osmosis membranes. Among them, SiO2 nanomaterials have attracted widespread attention in the field of forward osmosis membrane modification due to their unique physical and chemical properties, such as high specific surface area, good chemical stability, biocompatibility, and tunable surface charge.

[0005] When SiO2 nanomaterials are combined with forward osmosis membranes, they can significantly improve membrane performance. For example, the high specific surface area of ​​SiO2 nanomaterials can provide more adsorption sites for water molecules, thereby increasing the membrane's hydrophilicity, accelerating the transport rate of water molecules, and thus increasing the membrane's water flux. Furthermore, their surface charge properties can effectively inhibit the adsorption and deposition of pollutants on the membrane surface through electrostatic repulsion, enhancing the membrane's anti-fouling properties. However, current methods for incorporating SiO2 into forward osmosis membranes have several limitations. While traditional physical blending methods are relatively simple to operate, SiO2 nanoparticles tend to agglomerate during the preparation process, making uniform dispersion in the polymer matrix difficult. This not only leads to an uneven membrane structure but also affects the overall performance of the membrane, preventing the full realization of the advantages of SiO2 nanomaterials. While chemical grafting methods can form relatively stable chemical bonds between SiO2 and polymers, improving their binding strength, these methods typically require complex chemical reaction steps and harsh reaction conditions, impose high equipment requirements, and are difficult to control during the reaction process, resulting in increased preparation costs and hindering large-scale industrial production.

[0006] Developing a preparation method that can achieve uniform dispersion of SiO2 in forward osmosis membranes, enhance the interaction between SiO2 and polymers, and effectively remove small-molecule micropollutants, while also being simple, easy to operate, and capable of large-scale production, is of great significance for promoting the development and widespread application of forward osmosis technology. The proposed method for preparing SiO2 composite forward osmosis membranes based on in-situ polymerization and applying it to the removal of small-molecule micropollutants aims to address the aforementioned problems in the prior art and provide a new, more efficient and feasible approach for the preparation of forward osmosis membranes. Summary of the Invention

[0007] This invention aims to overcome the uneven dispersion of nanoparticles in forward osmosis membranes and the weak interaction between nanoparticles and polymers. It provides a composite forward osmosis membrane for removing small molecule micropollutants and a method for its preparation. The membrane exhibits excellent hydrophilicity and pure water flux, low reverse salt flux, and a high rejection rate for small molecule micropollutants. The method is simple, easy to operate, and readily scalable.

[0008] To achieve the above objectives, the following technical solutions are adopted:

[0009] A method for preparing a composite forward osmosis membrane for removing small molecule micropollutants comprises the following preparation steps:

[0010] S1. Preparation of aqueous solution: dissolve m-phenylenediamine, camphorsulfonic acid and triethylamine in aqueous solution and stir until completely dissolved;

[0011] S2. Preparation of organic phase solution: dissolve trimesoyl chloride and tetramethoxysilane in the organic phase and stir until completely dissolved;

[0012] S3, interfacial polymerization reaction: fix the basement membrane on the plate, add the aqueous solution, and then add the organic solution;

[0013] S4, heat treatment: the polyamide layer obtained in step S3 and the base membrane are transferred to an oven for heat treatment to obtain a forward osmosis membrane.

[0014] More specifically, in step S3, a base film is placed between two flat plates and fixed with a clamp; an aqueous solution and an organic solution are sequentially added to the fixed base film; the aqueous phase containing m-phenylenediamine and the organic phase solution containing trimesoyl chloride are instantly polymerized at the interface to form a polyamide layer. At the same time, tetramethoxysilane in the oil phase is hydrolyzed and condensed when encountering the aqueous phase to form silica containing hydroxyl groups; then, excess oil phase solution is poured out so that the polyamide layer formed by polymerization at the interface is evenly attached to the base film.

[0015] The invention uses m-phenylenediamine and trimesoyl chloride as raw materials to synthesize a polyamide layer, and uses camphorsulfonic acid and triethylamine to adjust the pH, so that the pH value of the solution in the subsequent free interface polymerization process is stabilized at a certain value.

[0016] The present invention may further comprise the following testing steps:

[0017] S5. Pollutant preparation: dissolve different pollutants in deionized water;

[0018] S6. Application: The forward osmosis membrane obtained in step S4 is used for separation of small molecule pollutants.

[0019] Furthermore, the inventors of this application added tetramethoxysilane to the oil phase, causing in-situ hydrolysis and condensation during the contact between the oil and water phases. This hydrolysis and condensation simultaneously formed hydroxyl-containing silica during the formation of the polyamide layer, thereby avoiding the uneven distribution of traditional nanoparticles in the polyamide layer and enhancing the interaction between SiO2 and the polymer. Subsequent desalination performance testing of the forward osmosis membrane prepared by the above preparation method revealed that, under optimal conditions, it maintained a low reverse salt flux while achieving a high water flux.

[0020] Preferably, the concentration of m-phenylenediamine in S1 is 1 wt%-4 wt%, the concentration of camphorsulfonic acid is 2 wt%-5 wt%, and the concentration of triethylamine is 1 w / v%-2.5 w / v%; the concentration of trimesoyl chloride in S2 is 0.05 wt%-0.3 wt%, and the concentration of tetramethoxysilane (TMOS) is 0.1 w / v%-1.2 w / v%.

[0021] By adjusting the content of TMOS, the size of the membrane pores can be controlled, thereby adjusting the water flux of the forward osmosis membrane.

[0022] Preferably, the aqueous phase in S1 is deionized water, and the organic phase in S2 is any one of water-insoluble organic solvents.

[0023] Preferably, in S3, the aqueous phase solution is poured onto the front surface of the flat membrane and allowed to soak for 5 minutes. The aqueous phase is poured out and then dried, and then the oil phase is poured to perform interfacial polymerization for 30s-180s.

[0024] Preferably, the heat treatment temperature in S4 is 60-100° C., and the heat treatment time is 8-10 min;

[0025] Preferably, the pollutant concentration prepared in S5 is 20ppm-100ppm.

[0026] The technical solution of the present invention also includes the composite forward osmosis membrane obtained by the above method.

[0027] The advantages of preparing SiO2 forward osmosis membrane based on in situ polymerization method proposed by the present invention are:

[0028] (1) The hydrolysis and condensation of tetramethoxysilane are used to make the generated nanoparticles evenly distributed. This uniform dispersion avoids the agglomeration of SiO2 nanoparticles, ensures the uniformity of the membrane structure, and makes the various properties of the membrane more stable and uniform;

[0029] (2) During the in-situ polymerization process, chemical bonding or strong physical interaction may form between SiO2 and the polymer, and the formed polyamide layer is tightly bonded to the base film and is not easy to fall off;

[0030] (3) The high specific surface area and surface functional groups of in situ synthesized SiO2 nanoparticles can regulate the transport path of water molecules and significantly increase the water flux of the forward osmosis membrane while ensuring a low salt flux;

[0031] (4) In situ synthesis of SiO2 nanoparticles regulates the formation process of the polyamide layer, realizes micropore regulation of the polyamide surface layer, and can achieve high retention of small molecule pollutants;

[0032] (5) The present invention does not aim to develop a high water flux forward osmosis membrane, but rather to ensure low reverse salt flux at the expense of a certain degree of water flux. It focuses on maintaining low reverse salt flux while ensuring a higher water flux, and by maintaining both properties within an appropriate range, it is more suitable for actual production applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The following is a further detailed description with reference to the accompanying drawings and embodiments of the present invention.

[0034] Figure 1 The invention relates to a preparation process for a composite forward osmosis membrane modified by adding TMOS into an organic phase.

[0035] Figure 2 Schematic diagram of the structure of polyamide containing hydroxy silicon.

[0036] Figure 3-1 This is a scanning electron micrograph of the surface of the unmodified polyamide membrane.

[0037] Figure 3-2 This is a scanning electron microscope image of the membrane surface when tetramethoxysilane is added to the organic phase at a concentration of 1%.

[0038] Figure 4 The effects of adding different concentrations of tetramethoxysilane on the performance of TFN forward osmosis membranes in Examples 9-12 are shown.

[0039] Figure 5 The figure shows the retention effect of different pollutants on the TFN forward osmosis membranes prepared by adding tetramethoxysilane at different concentrations in Examples 9-12. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the following description will be given in conjunction with exemplary embodiments or examples of the present invention. However, the present invention is not limited to the following examples. It is hereby stated that these examples are merely partial illustrations and do not limit the present invention. Unless otherwise specified, the raw materials used in the following examples or comparative examples are all commercially available conventional raw materials.

[0041] The following describes the methods used or possibly used in the embodiments or comparative examples of the present invention:

[0042] The operating environment of all experiments in the present invention is: temperature of 25° C., humidity of 50%, and normal pressure.

[0043] During the preparation of the polyamide separation layer, the interfacial polymerization conditions can be controlled by artificially adjusting the concentrations of raw monomers such as m-phenylenediamine and trimesoyl chloride to obtain an ultra-thin separation layer with optimal performance. The membrane prepared in this way can achieve higher water flux and lower reverse salt flux, as well as a higher retention rate for small molecules. In the following examples, we will focus on studying how changes in the concentrations of these two raw monomers, m-phenylenediamine and trimesoyl chloride, affect the membrane's water flux, reverse salt flux, and brine ratio; the effect of TMOS concentration on the membrane's water flux and reverse salt flux, as well as its effect on different small molecule pollutants.

[0044] Example 1

[0045] This embodiment provides a composite forward osmosis membrane for removing small molecule micropollutants and a preparation method thereof, which is carried out according to the following steps:

[0046] S1. Preparation of aqueous solution: 1% m-phenylenediamine, 4% camphorsulfonic acid, and 2.5% triethylamine were added to deionized water in sequence and stirred under magnetic stirring until completely dissolved to form a homogeneous solution;

[0047] S2. Preparation of an organic phase solution: 1% tetramethoxysilane was added to n-hexane, and then 0.05 wt% trimesoyl chloride was added thereto, and the mixture was stirred under magnetic stirring until completely dissolved to form a homogeneous solution;

[0048] S3, interfacial polymerization reaction: Fix the basement membrane on a flat plate with a clamp, add the aqueous solution, let the basement membrane soak for 5 minutes, then pour out the aqueous solution, dry until there is no obvious aqueous phase on the membrane surface, then add the organic phase solution, and pour out the organic phase after 30 seconds;

[0049] S4, heat treatment: taking out the composite forward osmosis membrane formed by the polyethersulfone base membrane and the interfacial polymerization, placing it in an oven at 80° C. and heat treating it for 10 minutes to obtain a composite forward osmosis membrane;

[0050] Example 2

[0051] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 2 wt %.

[0052] Example 3

[0053] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 3 wt %.

[0054] Example 4

[0055] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 4 wt %.

[0056] Example 5

[0057] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 2 wt % and the concentration of trimesoyl chloride is 0.05 wt %.

[0058] Example 6

[0059] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 2 wt % and the concentration of trimesoyl chloride is 0.1 wt %.

[0060] Example 7

[0061] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 2 wt % and the concentration of trimesoyl chloride is 0.2 wt %.

[0062] Example 8

[0063] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine in this embodiment is 2 wt % and the concentration of trimesoyl chloride is 0.3 wt %.

[0064] Example 9

[0065] The process of this embodiment is the same as that of Example 1, except that the concentration of m-phenylenediamine, trimesoyl chloride, and tetramethoxysilane in this embodiment is 2 wt %, 0.1 wt %, and 0.6 w / v %, and they are used to remove different pollutants.

[0066] Example 10

[0067] The process of this embodiment is the same as that of Example 1, except that the concentration of m-phenylenediamine, trimesoyl chloride and tetramethoxysilane in this embodiment is 2% by weight, 0.5% by weight and 0.8% by weight, respectively, and they are used to remove different pollutants.

[0068] Example 11

[0069] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine, trimesoyl chloride and tetramethoxysilane in this embodiment is 2 wt %, 0.1 wt % and 1 w / v %, and they are used to remove different pollutants.

[0070] Example 12

[0071] The process of this embodiment is the same as that of embodiment 1, except that the concentration of m-phenylenediamine, trimesoyl chloride and tetramethoxysilane in this embodiment is 2 wt %, 0.1 wt % and 1.2 w / v %, and they are used to remove different pollutants.

[0072] Performance Testing

[0073] 1. Electron microscopy test

[0074] Depend on Figure 3-1 It can be seen that the polyamide layer without the addition of tetramethoxysilane exhibits a "backbone" structure.

[0075] Depend on Figure 3-2 It can be seen that the surface of the forward osmosis membrane prepared by interfacial polymerization in the present invention is smooth and uniform, without obvious defects. After the addition of tetramethoxysilane, the surface structure of the membrane changes significantly, from a "spine" structure to a "large blade" structure, which allows the forward osmosis membrane to allow water to pass through while intercepting salt.

[0076] 2. Forward osmosis performance test: 1mol / L sodium chloride solution is used as the draw liquid, and deionized water is used as the raw material liquid. The raw material liquid pool and the draw liquid pool are placed on an electronic balance respectively. The flow rate of the raw material liquid and the draw liquid is controlled by a flow meter to be maintained at 150mL / min, and the stable operation time is constant to ensure that the flow rate on both sides of the system remains stable during the test. The raw material liquid mass value is recorded every minute by an electronic balance to track the amount of permeated water. At the same time, the ion concentration change of the raw material liquid is monitored in real time using a conductivity meter. The water flux (Jw) is used to characterize the water permeability of the membrane, which indicates the volume of water passing through the unit membrane area per unit time; the reverse salt flux (Js) is used to measure the retention performance of the membrane, which indicates the mass of salt passing through the unit membrane area per unit time; the relevant calculation equations are as follows:

[0077]

[0078] Where Jw is the water flux of FO, in L·m -2 ·h -1 ; Δm is the mass change of the raw material liquid, unit is g; ρ is the density of the raw material liquid, unit is g / ml; Am is the effective area of ​​the membrane, unit is cm 2 ; Δt is the test time, in h; Js is the reverse salt flux of the FO membrane, in g·m -2 ·h -1 ; V0 and V t They are the volume of the raw material liquid at the beginning of the test and the volume of the raw material liquid after the test is completed, in L; C0 and C t are the salt concentration of the raw material solution at the beginning of the test and the salt concentration of the raw material solution after the test is completed, respectively, in g / L.

[0079] 3. Pollutant removal performance test: 1 mol / L sodium chloride solution was used as the draw solution, and pollutants of different concentrations were used as the feed solution. Pure water in the contaminated water was drawn to the draw solution side by osmotic pressure, intercepting the pollutants. The experiment was run for 2 hours. Samples of the feed solution and the draw solution were taken before and after the experiment. The absorbance was measured using UV light, and the retention rate was calculated. The relevant calculation formula is as follows:

[0080]

[0081] Among them, C ds(f) is the final concentration of pollutants in the draw solution, in g / L, C fs(i) is the initial concentration of the contaminant in the feed solution, expressed in g / L. DF is the dilution factor, defined as the ratio of the final volume of the draw solution to the initial volume of the feed solution.

[0082] The forward osmosis membranes prepared in Examples 1 to 4 were subjected to flux tests, and the results are shown in the following table:

[0083] Table 1 Effect of different concentrations of m-phenylenediamine on forward osmosis membrane performance

[0084]

[0085] According to the above test results, when the concentration of m-phenylenediamine is 2 wt%, the pure water flux is higher, the reverse salt flux is smaller, and the brine ratio is smaller.

[0086] The forward osmosis membranes prepared in Examples 5 to 8 and Example 2 were subjected to flux tests, and the results are shown in the following table:

[0087]

[0088] According to the above test results, it can be seen that when the concentration of trimesoyl chloride increases to 0.1 wt %, the pure water flux is the highest, the reverse salt flux is smaller, and the brine ratio is small.

[0089] The forward osmosis membranes of Examples 9 to 12 and Example 6 were subjected to flux tests, and the results are shown in the following table:

[0090]

[0091] According to the above test results, it can be seen that when the tetramethoxysilane concentration increases to 1wt%, the pure water flux is the highest, the reverse salt flux is small, and the brine ratio is small. When the tetramethoxysilane concentration continues to increase, the pure water flux increases, but the salt flux increases sharply. Therefore, considering that both the water flux and the reverse salt flux are within the appropriate range, the tetramethoxysilane concentration of 1wt% in Example 11 is the most preferred, with a water flux of 11.33L·m -2 ·h -1 , salt flux 0.89 g·m -2 ·h -1 , the water flux of the forward osmosis membrane increased by 31.33%.

[0092] The pollutant removal test was performed on the forward osmosis membranes of Examples 9 to 12 and Example 6. The results are shown in the following table:

[0093]

[0094] The test results above show that as TMOS concentration increases, pollutant retention gradually decreases, but remains at a reasonable level. This means that while membrane water flux increases, reasonable pollutant retention is maintained. As the molecular weight of the pollutants increases from left to right, it is clear that the forward osmosis membrane can completely retain large molecular pollutants (within the measurable range). As the molecular weight decreases, the retention rate gradually decreases. This can be attributed to the hydrolysis and condensation of TMOS, which simultaneously forms hydroxyl silicon during the formation of the polyamide layer, leading to changes in the microporous structure. This in turn increases water flux and slightly decreases the retention rate, but it still remains at a high level.

[0095] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a composite forward osmosis membrane for removing small molecule micropollutants, comprising the following preparation steps: S1. Preparation of aqueous solution: dissolve m-phenylenediamine, camphorsulfonic acid and triethylamine in aqueous solution and stir until completely dissolved; S2. Preparation of organic phase solution: dissolve trimesoyl chloride and tetramethoxysilane in the organic phase and stir until completely dissolved; S3, interfacial polymerization reaction: fix the basement membrane on the plate, add the aqueous solution, and then add the organic solution; S4, heat treatment: the polyamide layer obtained in step S3 and the base membrane are transferred to an oven for heat treatment to obtain a forward osmosis membrane.

2. The method for preparing a composite forward osmosis membrane for removing small molecule micropollutants according to claim 1, wherein: In step S3, a base film is placed between two flat plates and fixed with a clamp; an aqueous phase solution and an organic phase solution are sequentially added to the fixed base film; the aqueous phase containing m-phenylenediamine and the organic phase solution containing trimesoyl chloride are instantly polymerized at the interface to form a polyamide layer. At the same time, tetramethoxysilane in the oil phase is hydrolyzed and condensed when encountering the aqueous phase to form silica containing hydroxyl groups; and then excess oil phase solution is poured out so that the polyamide layer formed by polymerization at the interface is evenly attached to the base film.

3. The method for preparing a composite forward osmosis membrane for removing small molecule micropollutants according to claim 2, wherein: In step S1, the concentration of m-phenylenediamine is 1 wt%-4 wt%, the concentration of camphorsulfonic acid is 2 wt%-5 wt%, and the concentration of triethylamine is 1 w / v%-2.5 w / v%. In step S2, the concentration of trimesoyl chloride is 0.05 wt%-0.3 wt%, and the concentration of tetramethoxysilane TMOS is 0.1 w / v%-1.2 w / v%.

4. The method for preparing a composite forward osmosis membrane for removing small molecule micropollutants according to claim 3, wherein: The aqueous phase in step S1 is deionized water, and the organic phase in step S2 is any one of water-insoluble organic solvents.

5. The method for preparing a composite forward osmosis membrane for removing small molecule micropollutants according to claim 3, wherein: In step S3, the aqueous phase solution is poured onto the front surface of the flat membrane and allowed to soak for 5 minutes. The aqueous phase is poured out and dried, and then the oil phase is poured in to perform interfacial polymerization for 30s-180s.

6. The method for preparing a composite forward osmosis membrane for removing small molecule micropollutants according to claim 3, wherein: The heat treatment temperature in step S4 is 60-100° C., and the heat treatment time is 8-10 minutes.

7. The method for preparing a composite forward osmosis membrane for removing small molecule micropollutants according to any one of claims 1 to 6, wherein: The following test steps are also included: S5. Pollutant preparation: dissolve different pollutants in deionized water; S6. Application: The forward osmosis membrane obtained in step S4 is used for separation of small molecule pollutants.

8. A forward osmosis membrane prepared by the method for removing small molecule micropollutants from a composite forward osmosis membrane according to any one of claims 1 to 6.